Legal liability for violation of hunting legislation in Russia, Belarus and Kazakhstan - Mukasheva, A.A.; Gorokhov, D.M.; Shingel, N.A. (Bulletin of the Karaganda University “Law Series”, 2023)
The article presents the results of a comprehensive study of the norms on legal liability for violation of the rules of hunting, illegal hunting, established in the three states of the EAEU. The relevance of the issue under consideration is due to the need to improve the theoretical aspects of legal liability for violation of hunting rules, illegal hunting, problems of proper qualification of illegal hunting, violations of hunting rules and related offenses. The main purpose of this study is to establish similar, comparable mechanisms of legal regulation in this area, to identify the specifics of the construction of liability rules in each state, to form common scientific and doctrinal views that justify the need for harmonization and unification of legislation. Conclusions are drawn that currently in Russia, Belarus and Kazakhstan similar legislation is in force, harmonized legal norms and terminology are applied, similar mechanisms of legal regulation of relations arising in connection with the implementation of legal liability for violation of hunting rules, illegal hunting are established. At the same time, differences are highlighted in establishing administrative and criminal liability, positive experience in building norms is noted, and its application in other states is proposed.